2016
DOI: 10.1186/s12906-016-1164-3
|View full text |Cite
|
Sign up to set email alerts
|

Activity of crude extracts from Brazilian cerrado plants against clinically relevant Candida species

Abstract: BackgroundMedicinal plants have traditionally been used in many parts of the world as alternative medicine. Many extracts and essential oils isolated from plants have disclosed biological activity, justifying the investigation of their potential antimicrobial activity. In this study, the in vitro antifungal activity of six Brazilian Cerrado medicinal plant species were evaluated against clinically relevant Candida species.MethodsThe crude extract plants were evaluated against American Type Culture Collection (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
(21 reference statements)
2
16
0
6
Order By: Relevance
“…However, no assays using Candida species have been carried out. Other species within the genera Eugenia, such as Eugenia dysenterica, have shown antimicrobial activity against several Candida species with MICs ranging between 125 and 500 µg/mL (Correia et al, 2016). These values are similar to those found in the present study using E. uniflora.…”
Section: Discussionsupporting
confidence: 89%
“…However, no assays using Candida species have been carried out. Other species within the genera Eugenia, such as Eugenia dysenterica, have shown antimicrobial activity against several Candida species with MICs ranging between 125 and 500 µg/mL (Correia et al, 2016). These values are similar to those found in the present study using E. uniflora.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the results observed by Holetz et al [ 27 ], Domingues et al [ 40 ], Paula et al [ 41 ] and Correia et al [ 42 ] showed good activity against yeasts of other species of the Myrtaceae family, suggesting that compounds of M. tomentosa , as avicularin can be used as a potential antifungal.…”
Section: Resultsmentioning
confidence: 95%
“…Several groups have been dedicated to the study of products of natural origin with antifungal action, in order to identify and isolate compounds with effective activity, safety in use and low toxicity against pathogenic fungi (Correia et al, 2016 ).…”
Section: Natural Products With Antifungal Properties Against mentioning
confidence: 99%
“…In relation to plants found mainly in Brazilian territory, Correia et al ( 2016 ) carried out an important study with different plants found in the Brazilian Cerrado, a region with an important number of species used in popular medicine, mainly in studies of essential oils with anti- Candida activity (Nordin et al, 2013 ; Correia et al, 2016 ).…”
Section: Natural Products With Antifungal Properties Against mentioning
confidence: 99%